Harnessing open account trade – A major enabler for illicit financial flows from developing countries: Can blockchain technology come to the rescue? Will the African Continental Free Trade Area leverage its Digital Trade Protocol? - Yuefen Li (South Centre, 2025)
The current geopolitical landscape has made domestic resource mobilization an even more important imperative for developing countries. In this context, it is more urgent than ever to combat illicit financial flows (IFFs) whose staggering amount from developing countries has outstrippedthecombinedsum of official development assistance (ODA) and foreign direct investment (FDI) going into the developing world. The IFFs from the financial channel is significant, but the greater proportion of IFFs actually stems from trade channels rather than from financial channels. It is particularly concerning that the flexibility and legitimacy of international trade have been exploited to cover IFFs. Trade mis-invoicing is the largest component of IFFs from developing countries. A major reason for trade being used to undertake illicit, fraudulent or criminal activities is because 80%-85% of the more than US 24 trillion international trade is conducted via open account trade (OAT), which has minimum scrutiny as it is conducted on a bilateral basis between the importer and exporter, not transparent and with minimal involvement of the financial institutions and customs authorities. OAT payment does not require documents to prove quality, quantity and other information about the product being shipped and is made through automatic payment systems which lack the oversight provided by any third party. OAT gives trade mis-invoicing great ease, flexibility, minimal cost and minimal risk. Therefore, if the world is serious about combatting IFFs, it is urgent and imperative to close loopholes in the OAT for IFFs, making it transparent, trackable and involving third party monitoring and scrutiny. The functionalities and features of Blockchain technology (BCT), though its implementation is still nascent, can be a good candidate to make OAT more modern, transparent to regulators, traceable, more efficient and above all minimize IFFs. The goals of the African Continental Free Trade Area (AfCFTA)'s Digital Trade Protocol (DTP) include boosting intra-African trade through unifying and harmonizing regulatory framework for Africa's digital economy and regional trade, promoting cross-border data flows and paperless trade, and enhancing cybersecurity measures. The exploration of Blockchain adoption to reduce OAT's risks for IFFs and make trade more effective aligns well with DTP's goals.
Keywords: 300; African Continental Free Trade Area (AfCFTA); Blockchain; Digital Trade Protocol; Illicit Financial Flows (IFFs); International Trade; Open Account Trade; Trade Finance; Trade Misinvoicing